AB1305 EVALUATION OF SERUM LEVELS OF ASC FOR THE DIAGNOSIS AND MONITORING OF CRYOPYRIN ASSOCIATED PERIODIC SYNDROMES (CAPS). (June 2019) - Carbone, Fortunata; Micillo, Teresa; Cantarini, Luca; Alessio, Maria; Olivieri, Alma Nunzia; Gicchino, Maria Francesca; Insalaco, Antonella; Maggio, Maria Cristina; Lucherini, Orso Maria; Scarpioni, Roberto; Piga, Matteo; Angioni, Maria Maddalena; et al.
Abstract : Background: Dominantly gain-of-function mutations in the NLRP3 gene lead to Cryopyrin associated periodic syndromes (CAPS) characterized by constitutive activation of the inflammasome, increased secretion of interleukin (IL)-1beta and IL-18, and systemic inflammation. IL-1beta and active caspase-1 subunits are released in the serum together with the oligomeric particles of the adaptor ASC (apoptosis-associated Speck-like protein with a caspase-recruitment domain) after activation of the inflammosome complex and, as a consequence, patients with CAPS show an increased serum concentration of ASC + particles. Objectives: Patients suffering from CAPS are characterized by clinical manifestation similar to other autoinflammatory diseases. This phenomenon together with the lack of specific laboratory tests makes difficult the diagnosis of CAPS. In this context the development of a test for the evaluation of serum ASC levels could provide novel biomarkers facilitating early disease diagnosis and able to monitor treatment responses. Methods: We analysed, with a novel ELISA assay, the levels of ASC particles in serum and plasma of normal subjects, CAPS patients and patients with autoimmune disorders (Multiple Sclerosis (MS), Type 1 Diabetes (T1D) and juvenile idiopathic arthritis), to confirm that ASC presence in the serum is not due to other chronic inflammatory processes characterizing autoimmunity. To evaluate the specificity of this biomarker in CAPS patients and not in individuals suffering from others inflammatory disorders, we also analysed sera from TNF receptor–associated periodic syndrome (TRAPS) patients. Results: ASC particles were higher in untreated CAPS patients with respect to healthy controls and patients suffering from MS and T1D. This tendency was also evident in patients with arthritis and TRAPS even if the difference was not statistically significant due to the small number of samples. In addition after pharmacological treatment there is a tendency to be confirmed through a reduction of ASC levels in CAPS patients. Conclusion: These data suggest that ELISA quantitation of ASC protein could represent a novel and additional strategy for the diagnosis and monitoring of CAPS. Disclosure of Interests: Fortunata Carbone: None declared, Teresa Micillo: None declared, Luca Cantarini: None declared, Maria Alessio: None declared, Alma Nunzia Olivieri: None declared, Maria Francesca Gicchino: None declared, Antonella Insalaco: None declared, Maria Cristina Maggio: None declared, Orso Maria Lucherini: None declared, Roberto Scarpioni: None declared, Matteo Piga: None declared, Maria Maddalena Angioni: None declared, Laura Obici: None declared, Antonella Simpatico: None declared, Pietro Leccese: None declared, Rita Consolini: None declared, Raffaele Manna: None declared, Paolo Sfriso: None declared, Sara Bindoli: None declared, Paola Galozzi: None declared, Ida Orlando: None declared, Sabrina Chiesa: None declared, Marco Gattorno Grant/research support from: MG has received unrestricted grants from Sobi and Novartis, Giuseppe Matarese Grant/research support from: Matarese reports research grants from Merck-Serono, Biogen Idec, Novartis and IBSA.